Schematic Representation of Bridging Artistic Skills and Leadership Styles - Qistina Donna, Lee Abdullah; Varatharajoo, Kashini Devi (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Leadership in this digital era is currently gaining lots of attention from all over the world including Malaysia. It is like a life to all organizations as it is merely impossible to move forward without leadership. This 21st century world and generation demand for a more different leadership practice which is more flexible. Basically, it all lies in the hands of a leader on how strategic the leadership is going to be and how well a team’s talent can be extracted. This paper presents a conceptual framework that studies the artistic skills and leadership characteristics to be included in the leadership styles. This paper also addresses the independent variables and the dependent variables which formed the whole framework. Systematic review methodology is employed whereby data are obtained from evidenced literatures. The justification behind choosing each and every variables are provided based on valid literature sources. Art is being bridged into leadership for a newer change and experience. Explanations are also provided on how this framework actually works. This framework serves as guideline which is applicable to all organizations in the country. The main aim of this paper is to suggest a newer practice of leadership to bring a new and better change to the organization and country.